2005
DOI: 10.1002/cne.20633
|View full text |Cite
|
Sign up to set email alerts
|

Differential distribution of release‐related proteins in the hippocampal CA3 area as revealed by freeze‐fracture replica labeling

Abstract: Synaptic vesicle release occurs at a specialized membrane domain known as the presynaptic active zone (AZ). Several membrane proteins are involved in the vesicle release processes such as docking, priming, and exocytotic fusion. Cytomatrix at the active zone (CAZ) proteins are structural components of the AZ and are highly concentrated in it. Localization of other release-related proteins including target soluble N-ethylmaleimide-sensitive-factor attachment protein receptor (t-SNARE) proteins, however, has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 85 publications
9
79
0
Order By: Relevance
“…Preferential colocalization of Kir3.2 and GABA B1 on dendritic spines of CA1 pyramidal cells To directly investigate the colocalization of Kir3.2 and GABA B1 in subcellular compartments of CA1 pyramidal cells, we performed double-and triple-labeling immunocytochemistry by using the highly sensitive SDS-digested freeze-fracture replica immunolabeling technique (Hagiwara et al, 2005;Tanaka et al, 2005). Consistent with the results of preembedding experiments, strong immunolabeling for Kir3.2 was found postsynaptically.…”
Section: Enrichment Of Kir32 Around Excitatory Synapses On Dendriticmentioning
confidence: 67%
“…Preferential colocalization of Kir3.2 and GABA B1 on dendritic spines of CA1 pyramidal cells To directly investigate the colocalization of Kir3.2 and GABA B1 in subcellular compartments of CA1 pyramidal cells, we performed double-and triple-labeling immunocytochemistry by using the highly sensitive SDS-digested freeze-fracture replica immunolabeling technique (Hagiwara et al, 2005;Tanaka et al, 2005). Consistent with the results of preembedding experiments, strong immunolabeling for Kir3.2 was found postsynaptically.…”
Section: Enrichment Of Kir32 Around Excitatory Synapses On Dendriticmentioning
confidence: 67%
“…By performing SDS-digested freeze-fracture replica immunolabeling (Hagiwara et al, 2005;Kulik et al, 2006), we found ␤1-integrin in presynaptic compartments of CA1 synapses. Anti-SNAP25 labeling was used to identify presynaptic compartments (Fig.…”
Section: Presynaptic Localization Of ␤1-integrin In Ca1 Synapsesmentioning
confidence: 93%
“…An antibody against vesicular glutamate transporter (vGluT) 2 raised in a guinea pig was used to mark the RG fibers with anti-guinea pig secondary antibody conjugated with 10 nm gold particles (BBI). Although vGluTs are vesicular proteins, they are often detected on presynaptic plasma membrane and thus have been used to identify the origin of presynaptic profiles (Hagiwara et al, 2005;Masugi-Tokita et al, 2007). For labeling of glial glutamate transporters GLT-1 and GLAST, rabbit antibodies against GLT-1 and GLAST, respectively, were used in combination with the vGluT2 antibody.…”
Section: Methodsmentioning
confidence: 99%